Problematika Pembelajaran Daring Di Rumah Selama Masa Pandemi Pada Anak Kelas B Tkit Yaumi Fatimah Pati - Adin Suryadin (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
Parents of guardians of students during this pandemic experienced many problems guiding the online learning process at home, especially kindergarten-age children who were still unstable in their learning behavior, the purpose of this study was to find out the extent of online problems at home and how the solutions were made by parents. This research method used a qualitative method with an open-endeed questionnaire instrument and the research subjects were all parents of class B students of TKIT Yaumi Fatimah Pati. The research results from the questionnaires distributed 25 open questionnaires and 20 questionnaires returned. The research results of the dominant sequence of problems are difficulties in arranging learning assistance schedules at home with children's learning time, difficulties in handling children to study at home, difficulties in understanding the material and difficulties in how to convey lesson material to children. The solution taken: arranging the activity schedule with the child's study schedule, bringing in an accompanying teacher at home or a relative who can accompany their child at home.